Taking the First Step to Facilitate Trade in Sudan : Setting Up a National Committee on Trade Facilitation - Adam, Ali Giddo (International Finance Corporation, Washington, DC, 2017)
The Republic of Sudan’s seaports used to be known for congestion resulting from the slow processing of imported goods. In response, the government created an ad hoc National Committee on trade facilitation to help streamline the processing of goods coming in and to facilitate trade. This smart lesson describes the steps taken in setting up the National Committee on Trade Facilitation and the challenges involved.